2018
DOI: 10.1080/25726668.2018.1451611
|View full text |Cite
|
Sign up to set email alerts
|

Potential of on-board energy recovery systems to reduce the costs of diesel–electric mine truck haulage

Abstract: On-board energy recovery systems (ERSs) are expected to reduce fuel consumption of open-pit mine haul trucks. However, the additional mass of an ERS would reduce the truck's payload, hence reducing productivity, effectively increasing other haul-related costs. Using a simulation program incorporating appropriate models for a diesel-electric mine haul truck, capital costs, operating costs and four energy recovery technologies, this paper investigates how various ERS technologies would affect overall haulage cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Terblanche et al (2018) examined the effect of installing an energy recovery system on the overall cost of mining a ton for a haulage truck using various energy recovery system technologies, different operating strategies and different depths of mine during the first year of operation for the truck. They concluded that the use of appropriate technology and energy recovery system could have significant potential to reduce haulage costs over a wide range of depths, especially if an energy reinjection strategy were used which reduces cycle time.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Terblanche et al (2018) examined the effect of installing an energy recovery system on the overall cost of mining a ton for a haulage truck using various energy recovery system technologies, different operating strategies and different depths of mine during the first year of operation for the truck. They concluded that the use of appropriate technology and energy recovery system could have significant potential to reduce haulage costs over a wide range of depths, especially if an energy reinjection strategy were used which reduces cycle time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The amount of cargo a dump truck can carry is called the capacity, which affects the fuel consumption of the vehicle (Dindarloo and Siami-irdemoosa, 2016; Siami-irdemoosa and Dindarloo, 2015; Terblanche et al , 2018; Terblanche et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some cases, dump trucks can generate a positive energy balance of 200 kWh daily [21]. Other studies on mining dump truck's regenerative breaking can also be seen in [22][23][24]. Depending on the road slope, electric trucks can even provide hydropower, by transporting water down the mountains [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, such installation implies a reduction in payload. Our previous work demonstrated that an appropriate ERS can reduce the fuel usage per tonne of material extracted (Terblanche et al 2018a), and for a fixed depth of pit can be expected to reduce the haulage cost (Terblanche et al 2018b) despite the payload loss. This work also demonstrated that the fuel savings and cost reduction for a particular depth of mine would be dependent on the size of the ERS.…”
Section: Introductionmentioning
confidence: 99%
“…Terblanche et al (2018a) show based on a simulation study, that an ERS of appropriate technology and size can be expected to provide as much as a 16% reduction in specific fuel consumption for a range of bench depths. Terblanche et al (2018b) show that using recovered energy to increase power available to the wheels during acceleration and ramp ascent may be able to more than compensate for the loss in payload caused by the ERS. The reduced cycle time could potentially lead to an overall reduction in haul costs and not only as a function of a reduction in fuel costs.…”
Section: Introductionmentioning
confidence: 99%